Incremental prognostic value of left atrial reservoir strain after ST-segment elevation myocardial infarction for the prediction of new-onset atrial fibrillation - Caunite, Laima; Myagmardorj, Rinchyenkhand; Galloo, Xavier; Laenens, Dorien; Stassen, Jan; Nabeta, Takeru; Yedidya, Idit; Meucci, Maria Chiara; Kuneman, Jurrien H.; van den Hoogen, Inge J.; van Rosendael, Sophie E.; Wu, Hoi W.; et al. (Springer Nature, 2025)
New-onset atrial fibrillation (AF) affects up to 21% of ST-segment elevation myocardial infarction (STEMI) patients. The value of LA reservoir strain to predict new-onset AF in a STEMI population has not been thoroughly investigated. We aimed to explore the incremental value of LA reservoir strain for predicting new-onset AF post-STEMI. Data were analyzed retrospectively from an ongoing STEMI registry. LA reservoir strain < 23% on transthoracic echocardiography was used as threshold for impaired LA function. The endpoint was new-onset AF. In total, 1238 patients (age 60 ± 12 years, 75% male) were included. After a median follow-up of 23 months, 92 (7.4%) patients developed new-onset AF. A similar prevalence of LA volume index >= 34 ml/m2 was seen between post-STEMI patients who developed new-onset AF and those who did not. In contrast, impaired LA reservoir strain was 1.5 times more common in individuals who developed AF (72% versus 48%; p < 0.001). Cumulative, event-free survival rates at five years in patients with preserved versus impaired LA reservoir strain were 93% versus 84%, respectively (log-rank χ2 = 19.81; p < 0.001). On multivariate Cox regression analysis LA reservoir strain remained significantly associated with new-onset AF (HR 0.97 (95% CI: 0.94-0.99); p = 0.025). Addition of LA reservoir strain provided incremental prognostic value over baseline clinical and echocardiographic risk markers (χ2 56.93 vs. 59.98; p = 0.013). Impaired LA reservoir strain was 1.5 times more common in patients who experienced new-onset AF post-STEMI, and was of incremental value for predicting the development of AF after adjusting for clinical and echocardiographic risk factors.Graphical abstractImpaired LA reservoir strain was 1.5 times more common in patients who experienced new-onset AF post-STEMI, and was of incremental value for predicting the development of AF.